2017
DOI: 10.18410/jebmh/2017/1169
|View full text |Cite
|
Sign up to set email alerts
|

Parenting and Its Influence on Child Behaviour

Abstract: BACKGROUNDParenting is the process of giving care to the young and preparing them to face the challenges of life. Diana Baumrind introduced the models of parenting, authoritative, authoritarian and permissive depending on the level of demandingness and responsiveness. Defective parenting is associated with problem behaviours in children. This study was undertaken to find out which parenting style is least associated with behavioural problems and what are the problems associated with the different parenting sty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
3
1
0
Order By: Relevance
“…We found that when children were not exposed to any discipline from their caregivers, they were more likely to experience the majority of negative psychosocial outcomes. This finding is congruent with previous findings regarding of permissive parenting styles (e.g., Antony & Vadakedom, 2017) and suggests that children need structure and guidance as part of their development, and that neglectful parenting (i.e., letting children do anything they want without supervision and adequate discipline) can exert deleterious effects on children.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…We found that when children were not exposed to any discipline from their caregivers, they were more likely to experience the majority of negative psychosocial outcomes. This finding is congruent with previous findings regarding of permissive parenting styles (e.g., Antony & Vadakedom, 2017) and suggests that children need structure and guidance as part of their development, and that neglectful parenting (i.e., letting children do anything they want without supervision and adequate discipline) can exert deleterious effects on children.…”
Section: Discussionsupporting
confidence: 90%
“…Our results show strong support for this hypothesis, and are congruent with the literature on the link between authoritarian parenting styles, harsh discipline, and detrimental outcomes (Antony & Vadakedom, 2017). Children who experienced serious and minor physical punishment were more likely to struggle with 7 of the 10 negative outcomes that we measured.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Ketika orang tua dan anak berinteraksi secara positif, persepsi anak terbentuk, mereka dibimbing dan perilaku negatif mereka dikurangi, serta kemampuan dan keterampilan mereka ditingkatkan. (Jiji MaryAntony, 2017).…”
Section: Berkomunikasi Dengan Anakunclassified